Case report: A case of intercostal intramuscular hemangioma with sternal invasion - Liu, Dongdong; Bao, Yuchen; Wang, Yanzhe; Lu, Xiangjun; Shen, Jian; Huang, Siyuan; Zhao, Ming; Wang, Haitao (Frontiers in Oncology, 2024)
Background: Intramuscular hemangioma is a vascular malformation occurring in muscle tissues. It is most common in skeletal muscles of limbs, especially lower limbs in childhood. The intercostal intramuscular hemangioma with sternal invasion is very rare.The 47-year-old female patient was hospitalized due to "suddenly chest pain for 4 days".Chest contrast-enhanced CT indicated bony changes in the sternum, accompanied by soft tissue shadows in the posterior sternum and diaphragmatic angle.After admission, physical examination showed: peristernal tenderness, percussion pain, other no obvious positive signs. PET-CT examination indicated that there was a high possibility of benign sternal changes. No cancer cells were found by sternal puncture. Surgical biopsy was performed and pathological findings were consistent with intramuscular hemangioma.Intramuscular hemangioma with bone invasion is very rare, imaging examination is difficult to indicate obvious evidence, preoperative diagnosis is difficult, complete surgical resection is very important, more personalized treatment should be provided according to the overall situation of the patient.